Forming of Regional Regulations Based on Good Governance Principles: Efforts to Realize Quality Regulations - Syofyan Hadi (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2026)
Regional regulations should be designed to promote public welfare, not merely to maintain rigid social order. They must be formulated flexibly to adapt to evolving community needs. This research examines the position of Regional Regulations within Indonesia’s legal hierarchy, analyzes the application of good governance principles in their formation, and proposes a model for their development based on these principles. This study employs normative legal research using statutory and conceptual approaches. The results of this research indicate that Regional Regulations are basically formed as delegated legislation, not as main legislation. Consequently, Regional Regulations must conform to laws issued by the Central Government. Accordingly, their formation must incorporate good governance principles. These principles at least include transparency, meaningful public participation, and accountability. The proposed model comprises five stages: needs analysis through research; participatory drafting with impact analysis; democratic discussion; effective implementation; and periodic evaluationan impact analysis, discussing the Draft Regional Regulation democratically, implementing the Regional Regulation effectively, and evaluating Regional Regulation periodically.